Unravelling consciousness and brain function through the lens of time, space, and information - Luppi, Andrea I.; Rosas, Fernando E.; Mediano, Pedro A.M.; Demertzi, Athena; Menon, David K.; Stamatakis, Emmanuel A. (Trends in neurosciences (Regular ed.), 2024)
Perturbations of consciousness arise from the interplay of brain network architecture, dynamics, and neuromodulation, providing the opportunity to interrogate the effects of these elements on behaviour and cognition.Fundamental building blocks of brain function can be identified through the lenses of space, time, and information.Each lens reveals similarities and differences across pathological and pharmacological perturbations of consciousness, in humans and across different species.Anaesthesia and brain injury can induce unconsciousness via different mechanisms, but exhibit shared neural signatures across space, time, and information.During loss of consciousness, the brain’s ability to explore functional patterns beyond the dictates of anatomy may become constrained.The effects of psychedelics may involve decoupling of brain structure and function across spatial and temporal scales. Disentangling how cognitive functions emerge from the interplay of brain dynamics and network architecture is among the major challenges that neuroscientists face. Pharmacological and pathological perturbations of consciousness provide a lens to investigate these complex challenges. Here, we review how recent advances about consciousness and the brain’s functional organisation have been driven by a common denominator: decomposing brain function into fundamental constituents of time, space, and information. Whereas unconsciousness increases structure–function coupling across scales, psychedelics may decouple brain function from structure. Convergent effects also emerge: anaesthetics, psychedelics, and disorders of consciousness can exhibit similar reconfigurations of the brain’s unimodal–transmodal functional axis. Decomposition approaches reveal the potential to translate discoveries across species, with computational modelling providing a path towards mechanistic integration. Disentangling how cognitive functions emerge from the interplay of brain dynamics and network architecture is among the major challenges that neuroscientists face. Pharmacological and pathological perturbations of consciousness provide a lens to investigate these complex challenges. Here, we review how recent advances about consciousness and the brain’s functional organisation have been driven by a common denominator: decomposing brain function into fundamental constituents of time, space, and information. Whereas unconsciousness increases structure–function coupling across scales, psychedelics may decouple brain function from structure. Convergent effects also emerge: anaesthetics, psychedelics, and disorders of consciousness can exhibit similar reconfigurations of the brain’s unimodal–transmodal functional axis. Decomposition approaches reveal the potential to translate discoveries across species, with computational modelling providing a path towards mechanistic integration.